1992
DOI: 10.1046/j.1469-0705.1992.02010040.x
|View full text |Cite
|
Sign up to set email alerts
|

Depth of myometrial invasion in endometrial cancer: preoperative assessment by transvaginal ultrasonography and magnetic resonance imaging

Abstract: Depth of myometrial invasion in endometrial cancer correlates with pelvic lymph node metastases and tumor recurrence. Thirty patients diagnosed as having FIGO stage I endometrial carcinoma on the basis of D&C were evaluated preoperatively by magnetic resonance imaging (MRI); 14 cases of the same group were also evaluated by transvaginal ultrasound. The degree of invasion evaluated by MRI and transvaginal sonography was compared to the pathological specimens. MRI was successful in evaluating myometrial invasion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
1
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 0 publications
2
23
1
2
Order By: Relevance
“…Relatively small-scale prospective studies have compared the diagnostic accuracies of TVS and MRI in the preoperative local staging of endometrial cancer, with conflicting results. 8,9 A recent study comparing TVS and MRI determined no difference in diagnostic accuracy for assessment of any invasion. 18 In addition to TVS and MRI, the present study has also evaluated the depth of myometrial evaluation with frozen section and Color Doppler sonography.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Relatively small-scale prospective studies have compared the diagnostic accuracies of TVS and MRI in the preoperative local staging of endometrial cancer, with conflicting results. 8,9 A recent study comparing TVS and MRI determined no difference in diagnostic accuracy for assessment of any invasion. 18 In addition to TVS and MRI, the present study has also evaluated the depth of myometrial evaluation with frozen section and Color Doppler sonography.…”
Section: Discussionmentioning
confidence: 99%
“…There are few prospective studies that compared the diagnostic accuracies of TVS and MRI in the preoperative local staging of endometrial carcinoma. 8,9 However, there has been no prospective comparison of the accuracy of TVS, MRI, and intraoperative frozen section in the assessment of myometrial invasion. There is also a debate about assessment of myometrial invasion with transvaginal Color Doppler ultrasonography (TV-CDU).…”
mentioning
confidence: 99%
“…Ultrasound is the conventional first‐line imaging investigation in patients suspected of endometrial cancer clinically. However, there are conflicting opinions in the use of ultrasound in preoperative staging assessment: Kim et al and Yamashita et al advocate MRI, in which they have demonstrated better staging accuracy, whereas Cagnazzo et al and Delmaschio et al found very similar staging accuracies between the two techniques (28,35–37) . Zarbo et al advocated using MRI only in cases where deep invasion is suspected on ultrasound (38) .…”
Section: Discussionmentioning
confidence: 99%
“…2 irregularity of endomyometrial interface indicate abnormality. 15 When fluid was present in the uterine cavity, size of the anechoic area was subtracted from the total thickness. Patients with suboptimal visualization of endometrium were excluded from the study group.…”
Section: Methodsmentioning
confidence: 99%